Institutional Complexity in Schools: Reconciling Clashing Logics Through Technology? - Gullberg, Cecilia; Svensson, Jenny (Scandinavian Journal of Public Administration, 2020)
The article analyses the introduction and use of an IT platform in two Swedish schools. The aim is to examine the role of information systems in shaping institutional complexity, and the research questions addressed are: what logics are manifested through the use of the system and how do they interact with each other in relation to teachers’ emerging work practices? The article is based on a qualitative case study of how teachers and principals perceive and use the system, and it combines theoretical thinking on institutional logics and complexity with ideas on materiality and its role in organisational change. An analysis of three teacher practices that are emerging with use of the system enables a discussion of the presence and, notably, interplay of three primary logics. Logics of professionalism, bureaucracy and management are shown to interrelate in competitive but, primarily, cooperative ways. The very materiality of the IT system is shown to attenuate experiences of incompatibilities between logics and facilitate the management of different logics when they are actually perceived to be incompatible. Contrary to what much previous literature on institutional complexity in the field of education suggests, we therefore argue that institutional complexity may facilitate and enrich teachers’ practices instead of merely constituting a hindrance.